Multicopy subtelomeric genes underlie animal infectivity of divergent Cryptosporidium hominis subtypes - Wanyi Huang; Wei He; Yue Huang; Yongping Tang; Ming Chen; Lianbei Sun; Zuwei Yang; Tianyi Hou; Huimin Liu; Haoyu Chen; Tianpeng Wang; Na Li; et al. (Nature Communications)
Abstract The anthroponotic Cryptosporidium hominis differs from the zoonotic C. parvum in its lack of infectivity to animals, but several divergent subtypes have recently been found in nonhuman primates and equines. Here, we sequence 17 animal C. hominis isolates and generate a new IbA12G3 genome at the chromosome level. Comparative analysis with 222 human isolates shows significant genetic divergence of the animal isolates, with genetic recombination among them. They have additional subtelomeric insulinase and MEDLE genes. In interferon-γ knockout mice, three monkey isolates show differences in infectivity and induce higher and longer oocyst shedding than a reference C. parvum isolate. Deletion of the MEDLE genes significantly reduces the growth and pathogenicity of a virulent strain in mice. Co-infection of two fluorescence-tagged C. hominis subtypes produces bicolored oocysts, supporting the conclusion that mixed subtype infections can lead to genetic recombination. These data provide insight into potential determinants of host infectivity in Cryptosporidium, and a convenient animal model for biological studies of C. hominis.